Solar Thermal Power: Appraisal of Solar Power Towers - Shatnawi H.; Lim C.W.; Ismail F.B. (EDP Sciences, 2023)
Heat transfer; Solar energy; Central receiver system; Fundamental component; High-temperature power; Receiver design; Solar power tower; Solar power tower plants; Solar thermal power; Volumetric receivers; Heat flux